Analysis of production risk and technical efficiency amongst smallholder livestock farmers in Botswana - Chube, Boitshepo (2019)
Achieving full efficiency is what every farmer desires to attain however due to constraints that they are faced with this is usually not possible. This study uses cross-section data to identify the shocks or risks that Botswana’s smallholder livestock producers are exposed to as well as their coping strategies. At the outset a sample of 540 observations which includes large and small beef producers are used but the econometric model estimated in the thesis is only limited to small beef producers. Furthermore, the study seeks factors that determine technical efficiency amongst small beef producers. The preliminary estimation of the Just-Pope production function did not lead to interpretable econometric results and for this reason, a change had to be made in the adopted empirical model. An alternative stochastic production model has been implemented empirically and estimated using a maximum likelihood (ML) estimation approach. The empirical results show that herd size and off-farm income reduce technical efficiency, an increase rainfall and household size were found to increase inefficiency. Moreover, production risk increases with an increase in maximum temperature but reduces with an increase in rainfall. The mean technical efficiency for the study area is 0.837.